Histone Deacetylase (HDAC) Inhibitors as a Novel Therapeutic Option Against Fibrotic and Inflammatory Diseases - Maria A. Theodoropoulou; Christiana Mantzourani; George Kokotos (Biomolecules, 2024)
Histone deacetylases (HDACs) are enzymes that play an essential role in the onset and progression of cancer. As a consequence, a variety of HDAC inhibitors (HDACis) have been developed as potent anticancer agents, several of which have been approved by the FDA for cancer treatment. However, recent accumulated research results have suggested that HDACs are also involved in several other pathophysiological conditions, such as fibrotic, inflammatory, neurodegenerative, and autoimmune diseases. Very recently, the HDAC inhibitor givinostat has been approved by the FDA for an indication beyond cancer: the treatment of Duchenne muscular dystrophy. In recent years, more and more HDACis have been developed as tools to understand the role that HDACs play in various disorders and as a novel therapeutic approach to fight various diseases other than cancer. In the present perspective article, we discuss the development and study of HDACis as anti-fibrotic and anti-inflammatory agents, covering the period from 2020–2024. We envision that the discovery of selective inhibitors targeting specific HDAC isozymes will allow the elucidation of the role of HDACs in various pathological processes and will lead to the development of promising treatments for such diseases.